(untitled) (INNOVATIVE ECONOMY, 2020)
Ivanyshyn V.V., Pecheniuk A.P. RURAL GREEN TOURISM AS A FORM OF SOCIAL ENTERPRISE Purpose. The aim of the article is the formation of optimal adaptive models of development of rural green tourism, based on the principles of social entrepreneurship. Methodology of research. The study used a comparative method – to determine the characteristics of social entrepreneurship and rural green tourism; the method of a systematic approach – when considering social entrepreneurship and rural green tourism as systems that consist of a certain number of interconnected elements, interacting and affecting the effectiveness of social and economic development; the method of scientific abstraction – in the allocation in the phenomena studied strong, stable, typical, which allowed to formulate in a generalized form, certain models of economic relations. Findings. Rural green tourism on the subject of compliance with the objectives of social entrepreneurship is investigated. Characteristic features and common features of these phenomena are determined. The problems of the development of social entrepreneurship and rural tourism in Ukraine are outlined and analyzed. Sources of financing of social entrepreneurship are considered. The proposals on the use of mechanisms for combining the development of rural green tourism in the structure of social entrepreneurship have been formed. Originality. The proposals on the formation of adaptive models of development of rural green tourism based on social entrepreneurship are substantiated. Identified in the study and informed common features green tourism activities and social enterprises that facilitate the integration of green tourism sector in the social enterprise model and can form a common vector for sustainable development of the Ukrainian village, which will be the basis to develop an effective national strategy for rural development. Practical value. The results of the study can be one of the directions of development of an effective national strategy for the development of rural areas, based on entrepreneurial activity and education, which will ultimately be manifested by the social effect of the proposals put in place. Key words: social entrepreneurship; rural green tourism; social stability; models of development; forms of integration; social effect.